Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Number: 4
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; cours; discipline; droits des femmes*; europe; fem3400; femmes* musulmanes; france; histoire et politique; phi4336; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis